Belief in school meritocracy as a system-justifying tool for low status students - Wiederkehr, Virginie; Bonnot, Virginie; Krauth-Gruber, Silvia; Darnon, Céline (Frontiers in Psychology, 2015)
The belief that, in school, success only depends on will and hard work is widespread in Western societies despite evidence showing that several factors other than merit explain school success, including group belonging (e.g., social class, gender). In the present paper, we argue that because merit is the only track for low status students to reach upward mobility, Belief in School Meritocracy (BSM) is a particularly useful system-justifying tool to help them perceive their place in society as being deserved. Consequently, for low status students (but not high status students), this belief should be related to more general system-justifying beliefs (Study 1). Moreover, low status students should be particularly prone to endorsing this belief when their place within a system on which they strongly depend to acquire status is challenged (Study 2). In Study 1, high status (boys and high SES) were compared to low status (girls and low SES) high school students. Results indicated that BSM was related to system-justifying beliefs only for low SES students and for girls, but not for high SES students or for boys. In Study 2, university students were exposed (or not) to information about an important selection process that occurs at the university, depending on the condition. Their subjective status was assessed. Although such a confrontation reduced BSM for high subjective SES students, it tended to enhance it for low subjective SES students. Results are discussed in terms of system justification motives and the palliative function meritocratic ideology may play for low status students.